A Welfare and Pass-Through Effects of Regulations within Imperfect Competition - Walid Y Alali; Haider Ellalee (ZBW – Leibniz Information Centre for Economics, 2022)
Abstract: This paper furnishes an inclusive framework to examine the welfare effects of the interventions of multiple policies, and other exterior alterations under imperfect competition and an assertion on particular and .the leading case of the ad valorem taxes. In particular, for the tax pass-through, we furnish ``sufficient statistics” equations for measures of the two welfare under the demand of the impartially general class, market competition and production cost. The measures are i) Public fund of the marginal value, ii) Incidence. We start with the status of symmetric firms' face up with both ad valorem taxes and unit tax to derive an empirically pertinent set of formulas and simple. Next, we make a substantial generalization of these results to include firm heterogeneity using the idea of tax revenue defined as a public function defined by a vector of policy instruments including governmental and non-governmental interventions and other non-tax costs.
Keywords: 330; Imperfect Competition; Pass-through; Marginal Value of Public; Funds; Incidence; Sufficient Statistics